THE PUBLIC PARTICIPATION IN SOLVING THE VIOLENCE PROBLEMS IN LOCAL POLITICS IN PATHUMTHANI AND AYUTTHAYA PROVINCE - เติมศักดิ์ ทองอินทร์, (Journal of MCU Social Science Review, 2020)
The objectives of the Public Participation in Solving the Violence Problems in Local Politics in Pathumthani and Ayutthaya Province were 1) The purpose is to study the reasons for public participation to local political violence. 2) To study the public participation in solving the problem and 3) to integrate Buddhadhamma to solve the problem. The research methodology was the consequential mixed research; quantitative and qualitative. Findings were as follows: the public participation in solving the violence problems in local politics before the elections, during the election and after the election are several parts. The violence occurred due to the candidate and private matter cannot be separated from each other. Because politicians want to be the represent the people in the Local administration organization. Politicians have to approach people to satisfy the public, seek the chance of political advantage, using an ingenious method and the use of methods that are legitimate and not legitimate. The public can participate in the adoption or rejection expressed by politicians to act as an agent of the public administration organizations. The overall quantitative research is already at a high level and can be applied the Buddhadhamma to solve the problem of violence in local politics.